Analysis of the Kulon Progo Bela-Beli Program on the Economy - Uswatun Khasanah; Diasa Karimahakim; Anas Usman Bello (Universitas Ahmad Dahlan, Yogyakarta, 2022)
Regional or local economic development is a process of involvement of local governments and elements of society in jointly managing local resources or potentials with the aim of creating new jobs that can stimulate economic and community growth as well as alleviating people in poverty. One of the efforts to overcome these problems is the